Contingency, Irony … Textuality: A Portrait of the Artist as a Young Man and Textual Criticism. Issue 1 (February 2020) - Creasy, Matthew
Abstract : This essay explores the representation of contingency within A Portrait of the Artist as a Young Man in relation to the textual history of James Joyce's novel. There is a fundamental split in this word between haphazard, chance forms of contingency and contingency as determining circumstances. First, I map these conflicting meanings on to Joyce's presentation of Stephen Dedalus and his drive towards artistic autonomy; then I use this tension to explore the textual condition of Joyce's novel, which seems, paradoxically, to demand a hyper-correct text in order to convey the vulnerability of printed works to unforeseen interventions.